Amoxicillin+clavulanic acid in community acquired pneumonia: Past, present, and future from an Indian perspective - Budhiraja, Sandeep; Agarwal, Akhil; Chugh, Yashpal; Gandhi, Alap; Kotak, Bhavesh (Asian Journal of Medical Sciences, 2022)
Community acquired pneumonia (CAP) is a major health problem in India with high morbidity and mortality. The threat posed by this infection is further intensified by the continued emergence of resistance to the currently available antibiotics. With a heritage of more than 24 years in India, amoxicillin+clavulanic acid is one of the most common antibiotics used for CAP. It was developed with an intent to sustain the efficacy of amoxicillin which was challenged due to the emergence of the beta-lactamase producing microorganism. Over a period, it has been included in national and international guidelines for the treatment of CAP. To assure the highest probability of clinical cure and to combat development of resistance: It is imperative for amoxicillin+clavulanic acid to reaffirm itself. Optimization of the PK/PD and higher dose of amoxicllin+clavulanic acid will tackle the burden of the future difficult to manage respiratory infections.